2007
DOI: 10.1002/jnr.21503
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and quercetin, two natural polyphenols, reduce apoptotic neuronal cell death induced by neuroinflammation

Abstract: Parkinson's disease (PD) is a movement disorder characterized by a progressive loss of nigrostriatal dopaminergic neurons. Microglia activation and neuroinflammation have been associated with the pathogenesis of PD. Indeed, cytokines have been proposed as candidates that mediate the apoptotic cell death of dopaminergic neurons seen in PD. In this study, we investigated the effect of two natural polyphenols, resveratrol and quercetin, on neuroinflammation. For glial cells, we observed that lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(197 citation statements)
references
References 76 publications
9
187
0
1
Order By: Relevance
“…Hence, modulation of NO production, glial signalling cascades and pro-inflammatory cytokines might result in suppression of neuro-inflammation and may ultimately protect against neurodegeneration. Although the neuroprotective effects of quercetin are found to be via its anti-oxidative and antiinflammatory capacity in an in vitro system of lipopolysaccahride-activated co-culture of microglial and neuronal cells (7,8), it is uncertain whether its mode of action in the in vivo PD model involves anti-inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, modulation of NO production, glial signalling cascades and pro-inflammatory cytokines might result in suppression of neuro-inflammation and may ultimately protect against neurodegeneration. Although the neuroprotective effects of quercetin are found to be via its anti-oxidative and antiinflammatory capacity in an in vitro system of lipopolysaccahride-activated co-culture of microglial and neuronal cells (7,8), it is uncertain whether its mode of action in the in vivo PD model involves anti-inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Q amplifies action of the cytostatic drug on cells of the sensitive line, which provides perspective for decreasing dosage of the drug. This might be particularly valuable that the synergistic effects of Q and DB in their antiproliferative and pro-apoptotic actions take place only in cases of neoplastic cells, while normal cells in parallel are protected, also against toxic action of cytostatic drugs [3,16,51].…”
Section: Discussionmentioning
confidence: 99%
“…For the last decades Q has been known as a strong antioxidant, an anti-inflammatory agent, a vaso-dilatatory compound, and an agent which decreases blood pressure and inhibits aggregation of blood platelets [1][2][3]. Also on multiple occasions Q was found to exert antineoplastic effects on all stages of carcinogenesis [1,2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in glial cells it was shown that quercetin can inhibit LPS-induced mRNA levels of two cytokines, i.e. TNF-and IL-1 (Bureau et al, 2008). It has already been shown that quercetin can inhibit the production as well as the gene expression of TNF-via modulation of NF-κB in human peripheral blood mononuclear cells (Nair et al, 2006).…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%